Patient Factors Affecting Emergency Department Utilization and Hospital Readmission Rates After Primary Anterior Cervical Discectomy and Fusion: A Review of 41, 813 cases. Issue 15 (1st August 2019) - Sheha, Evan D.; Salzmann, Stephan N.; Khormaee, Sariah; Yang, Jingyan; Girardi, Federico P.; Cammisa, Frank P.; Sama, Andrew A.; Lyman, Stephen; Hughes, Alexander P.
Abstract : Study Design: Retrospective database analysis. Objective: To identify preoperative risk factors for emergency department (ED) visit and unplanned hospital readmission after primary anterior cervical discectomy and fusion (ACDF) at 30 and 90 days. Summary of Background Data: Limited data exist to identify factors associated with ED visit or readmission after primary ACDF within the first 3 months following surgery. Methods: Patients undergoing ACDF from 2005 to 2012 were identified in the Statewide Planning and Research Cooperative System database. Multivariable regression models were created based on patient-level and surgical characteristics to identify independent risk factors for hospital revisit. Results: Of 41, 813 patients identified, 2514 (6.0%) returned to the ED within 30 days of discharge. Risk factors included age < 35, black race (OR 1.19), Charlson Comorbidity index score > 1, length of stay (LOS) greater than 1 day (OR 1.23), and fusion of > 2 levels (OR 1.17). Four thousand six hundred nine (11.0%) patients returned to the ED within 90 days. Risk factors mirrored those at 30 days. Patients having private insurance or those discharged to rehab were less likely to present to the ED. One thousand three hundred ninety-four (3.3%) patients were readmitted by 30 days. Risk factors included male sex, Medicare, or Medicaid insurance (OR 1.71 and 1.79 respectively), Charlson comorbidity index > 1, discharge to a skilled nursing facility (OR 2.90), infectious/pathologic (OR 3.296), or traumatic (OR 1.409) surgical indication, LOS > 1 day (OR 1.66), or in-hospital complication. 2223 (5.3%) patients were readmitted by 90 days. Risk factors mirrored those at 30 days. No differences in readmission were seen based on race or number of levels fused. Patients aged 18 to 34 were less likely to be readmitted versus patients older than 35. Conclusion: Insurance status, comorbidities, and LOS consistently predicted an unplanned hospital visit at 30 and 90 days. Although nondegenerative surgical indications and in-hospital complications did not predict ED visits, these factors increased the risk for readmission. Level of Evidence: 3 Abstract : The SPARCS database was used to evaluate the patient-level factors leading to ED utilization and unplanned readmission after ACDF at 30 and 90 days. Insurance status, comorbidities, and LOS consistently predicted an unplanned hospital visit at both timepoints. Nondegenerative surgical indications and in-hospital complications increased the risk for readmission.